Increased risk of perforated appendicitis in patients with schizophrenia and dementia: A population-based case-control study - Lin, Huang Ren (Medicine (Baltimore), 2020)
Previous studies have suggested that patients with psychotic or mental disorders are relatively pain insensitive, resulting in difficulties in the diagnosis of acute intra-abdominal diseases requiring emergency surgeries. We aimed to evaluate whether central nervous system (CNS) or mental disorders are associated with perforated appendicitis in patients with acute appendicitis. We conducted a population-based case-control study using Taiwan's National Health Insurance Research database. Patients aged >18 years who had been hospitalized with a diagnosis of acute appendicitis between 2000 and 2013 were identified. After 1:1 matching for age and sex, 2792 patients with perforated appendicitis (case group) and 2792 patients with nonperforated appendicitis (control group) were included. CNS disorders, mental disorders, pain control medication, and several comorbidities were analyzed for the odds of appendiceal perforation with 95% confidence interval (CI) using the multivariable logistic regression model. Schizophrenia and dementia were associated with a high risk of appendiceal rupture in patients with acute appendicitis, with an adjusted odds ratio of 2.01 for dementia (95% CI: 1.19–3.39, P = .009) and 4.8 for schizophrenia (95% CI: 1.62–14.19, P = .005). Other factors, such as other CNS disorders, comorbidities, and pain control medication, were not associated with the risk of perforated appendicitis. Dementia and schizophrenia are associated with perforated appendicitis in patients with acute appendicitis. This might be owing to altered pain perception, difficult symptom expression, and delayed hospitalization. Further studies are still needed to determine the underlying mechanism and confirm the causality.